Hybrid liquid crystalline zinc phthalocyanine@Cu2O nanowires for NO2 sensor application - Sisman, Orhan; Kilinc, Necmettin; Akkus, Unal Ozden; Sama, Jordi; Romano-Rodriguez, Albert; Atilla, Devrim; Gürek, Ayşe Gül (Elsevier Science Sa, 2021)
A novel organic-inorganic hybrid conductometric NO2 sensor has been introduced by depositing liquid crystalline zinc oktakisalkylthiophthalocyanine [(C6S)(8)PcZn] on the surface of Cu2O nanowires. Cu2O nano wires were synthesized by electrochemical anodization of Cu films on glass substrates. Surface structures of bare Cu2O and (C6S)(8)PcZn@Cu2O nanowires hybrid structures were monitored by scanning electron microscope (SEM). UV-vis spectrophotometer measurements revealed the heterostructure formation by comparing the absorption profiles of bare Cu2O nanowires, (C6S)(8)PcZn thin film, and (C6S)(8)PcZn@Cu2O hybrid nanowires. The interdigitated transducers (IDT) were used for conductometric gas measurements. The sensing properties of all samples were investigated towards 500 ppb, 1 ppm, 2 ppm, and 5 ppm NO2 under dry airflow in 30 degrees C, 50 degrees C, 100 degrees C, and 150 degrees C. The measurements at 150 degrees C were repeated for (C6S)(8)PcZn film and hybrid sample using the same concentrations of NO2 gas under 38 % relative humidity airflow. In addition, selectivity of hybrid sensor was confirmed with carbon monoxide (CO), hydrogen (H-2) and ethanol (C2H5OH) measurements. Our density functional theory calculations indicate that S atoms play a crucial role in improving the sensor response. The sensing properties and sensing mechanisms of samples were compared and discussed.
Keywords: Cuprous oxide nanowires; Metallophthalocyanines; Hybrid nanostructures; Density functional theory; NO2 detection